Evaluation in Language and Literature Learning in Elementary Schools - Ni Wayan Eka Widiastini; Ni Made Daini Sinta Sari; Mulyadin; Muhammad Hafizin (International Journal of Language and Literature, 2025)
In the context of the Merdeka Curriculum, the evaluation paradigm has shifted from merely measuring learning outcomes to authentic assessment that emphasizes students’ learning processes, performance, and reflection. This study aims to analyze the concepts, forms, principles, and implementation of language and literature learning evaluation in elementary schools based on recent scholarly literature. This research employed a library research method consisting of several stages, including the identification of data sources through scientific databases such as Google Scholar, ERIC, Scopus, and Garuda, as well as the selection of relevant articles using inclusion criteria focused on publications related to the evaluation of language and literature learning at the elementary school level. Data were collected through systematic documentation of research findings and relevant theoretical perspectives. The data were then analyzed using a content analysis approach to categorize the findings into several main themes, namely concepts, forms, principles, challenges, and recommendations for evaluation practices. The findings indicate that formative, summative, authentic, and project-based assessments have become dominant approaches that align with the principles of Merdeka Belajar. Teachers are required to possess a high level of assessment literacy in order to effectively evaluate both receptive and productive language skills in an integrated manner. The main challenges include teachers’ limited understanding of assessment practices, the suboptimal use of assessment rubrics, and the continued dominance of written tests in evaluation practices. Theoretically, this study contributes to enriching the conceptual discourse on the transformation of language and literature evaluation paradigms in the era of the Merdeka Curriculum. The findings also provide implications for the development of teacher training in assessment literacy, the design of performance-based digital evaluation media, and the strengthening of integrative assessment models that holistically evaluate both learning processes and outcomes.